4D‐Printing of Photoswitchable Actuators. Issue 10 (12th January 2021) - Lu, Xili; Ambulo, Cedric P.; Wang, Suitu; Rivera‐Tarazona, Laura K.; Kim, Hyun; Searles, Kyle; Ware, Taylor H.
Abstract: Shape‐switching behavior, where a transient stimulus induces an indefinitely stable deformation that can be recovered on exposure to another transient stimulus, is critical to building smart structures from responsive polymers as continue power is not needed to maintain deformations. Herein, we 4D‐print shape‐switching liquid crystalline elastomers (LCEs) functionalized with supramolecular crosslinks, dynamic covalent crosslinks, and azobenzene. The salient property of shape‐switching LCEs is that light induces long‐lived, deformation that can be recovered on‐demand by heating. UV‐light isomerizes azobenzene from trans to cis, and temporarily breaks the supramolecular crosslinks, resulting in a programmed deformation. After UV, the shape‐switching LCEs fix more than 90 % of the deformation over 3 days by the reformed supramolecular crosslinks. Using the shape‐switching properties, we print Braille‐like actuators that can be photoswitched to display different letters. This new class of photoswitchable actuators may impact applications such as deployable devices where continuous application of power is impractical. Abstract : Shape‐switching liquid crystal elastomers are formulated where light is used to trigger a shape change which is then stable indefinitely. The original shape can be recovered on heating. These materials can be 4D printed into reconfigurable Braille‐like actuators capable of displaying letters "L", "C" and "E" by switching the shape‐morphing of the Archimedean chord patterns with UV light and heating.